Pengaruh Word of Mouth: Keputusan Orang Tua Milenial dalam Memilih Sekolah Islam Terpadu - Fatiya Zahida; Mulyadi (LPPM Stikosa - AWS, 2025)
This study examines how word of mouth (WOM) influences millennial parents in Bandarlampung when selecting an Integrated Islamic School (SIT). Using a quantitative approach, data were collected from 61 respondents across six SITs. Validity and reliability tests confirmed the quality of the instrument (Cronbach’s Alpha = 0.901). Statistical analysis using ANOVA and simple linear regression revealed that WOM significantly affects school choice (F = 76.121, p < 0.001), with a strong correlation (R = 0.751) and R² = 0.563, indicating that WOM explains 56.3% of the variance in school choice decisions. Further analysis shows that interpersonal recommendations—particularly from friends (39.3%) and family (26.2%)—are more influential than information from social media (19.7%) or brochures (14.8%). These findings support the Source Credibility Theory, emphasizing that trusted sources have greater persuasive power. They also align with Social Influence and Diffusion of Innovations theories, demonstrating how community networks influence parental behavior, particularly among digital-native millennial parents. Practically, SITs should build strong parent communities, encourage testimonials both offline and online, and maintain high service quality to reinforce positive word of mouth (WOM). Managing Word of Mouth (WOM) strategically can increase school visibility and trustworthiness. This study contributes to understanding behavioral patterns among millennial parents in educational contexts. Future research may explore other influencing factors, such as educational values, digital engagement patterns, or comparisons across different school types and regions..